Integrating Logistics and Information Systems in Urban Waste Management: The Road to a Sustainable Smart City - Koman Gabriel; Krúpová Silvia (Logi)
The integration of logistics and information systems in urban waste management is a key step towards building sustainable smart cities. In the context of increasing urbanisation and environmental challenges, cities are forced to look for more efficient solutions for waste management. This paper explores how the interconnection of logistics and modern information technology can optimize waste collection, sorting and recycling processes, reduce operational costs and minimize negative environmental impacts. Using smart sensors, monitoring systems and analytical tools, it is possible to improve the planning of waste collection routes and predict the needs of different areas. The result is greater efficiency in urban waste management, leading to reduced landfill waste production and better use of recyclable materials. This article also highlights the need for coordinated cooperation between the public and private sectors, as well as the importance of a legislative framework that promotes technological innovation and environmental sustainability. Integrating these solutions into the infrastructure of modern cities contributes to their transition towards sustainable and smart urban ecosystems.